The war of the three Gods Romans, Persians, and the rise of Islam - Crawford, Peter (Skyhorse Publishing, 2014)
The War of the Three Gods is a military history of the Near and Middle East in the seventh century-with its chief focus on the reign of the Eastern Roman Emperor Heraclius (AD 610-641)-a pivotal and dramatic time in world history. The Eastern Roman Empire was brought to the very brink of extinction by the Sassanid Persians before Heraclius managed to inflict a crushing defeat on the Sassanids with a desperate, final gambit. His conquests were short-lived, however, for the newly converted adherents of Islam burst upon the region, administering the coup de grace to Sassanid power and laying sieg